Effect of leg wrapping on haemodynamics and associated complications in caesarean section: a randomised prospective study - Das, Prajnyananda; Swain, Sumita (International Journal of Research in Medical Sciences, 2016)
Background: Spinal anesthesia in cesarean section has a rapid onset of action, reliable and provides good surgical conditions, however there is risk of placental hypo-perfusion proportional to the degree of sympathetic block. Inspite of traditional preventive measures (fluid preload, fluid co-load, left lateral tilt, and ephedrine prophylaxis) post spinal hypotension is difficult to avoid. In this study efficiency of pre block leg wrapping in preventing hypotension and associated complications in parturients have been evaluated. Methods: 60 patients posted for elective cesarean section under spinal anesthesia of ASA grade Ι and ΙΙ under spinal anesthesia were allocated two groups with or without leg wrapping with elastic bandage. All of them received 10ml/kg ringer’s lactate preloading, spinal anaesthesia in sitting position and haemodynamic monitoring done. Complications like hypotension managed with intravenous phenylephrine. Results: There was statistically significant difference in degree of hypotension found between the two groups. Incidence of hypotension in Group A (leg wrapped) is 13.33% where as in group B (leg not wrapped) is 63.33%. There is significant difference in incidence of nausea, vomiting and shivering in both the groups. Conclusions: Leg wrapping with elastic crepe bandage is cheap, easy, readily available, non-invasive, and non-pharmacological method, can be recommended in addition with preload and left uterine displacement for preventing post spinal hypotension and its subsequent adverse effect on the mother as well as on a baby and can be of great value in routine practice.